Vaksin Covid-19 Sebagai Karya Paten Dalam TRIPs Agreement - Jose, Palti Josua; Berlianty, Teng; Kuahaty, Sarah Selfina (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2023)
The Covid-19 pandemic is a Public Health Emergency, a challenge for developing and underdeveloped countries to get a Covid-19 vaccine. Patent protection that is accommodated in the TRIPS Agreement is considered burdensome for vaccine accessibility, because it has a direct impact on increasing vaccine prices, making it difficult for some countries with low per capita incomes and lagging industries to reach them. The purpose of this paper is to determine the arrangement of patent rights based on the TRIPS Agreement. The research method used in this paper is normative juridical, namely by examining library data or materials in the form of primary legal materials and secondary legal materials. Then it will be described descriptively and given a conclusion. The strict patent system and the exclusive rights of patent holders contained in the TRIPS Agreement are barriers to reaching pharmaceutical inventions. Therefore, every country needs a National Emergency Plan that can accommodate health services such as vaccines. This can be implemented using a Compulsory License or Government Use (Patent Implementation by the Government) instrument.